Enhancement of the efficiency of polymer solar cells by blending Nb/ZnO nanoparticles into poly(3-hexylthiophene):[6,6]-phenyl C61-butyric acid methyl ester - Kruefu V. (2014)
Bulk-heterojunction (BHJ) solar cells utilizing P3HT:PCBM composite loaded with niobium-doped zinc oxide nanoparticles (Nb/ZnO NPs) produced by flame spray pyrolysis were fabricated. The devices loaded with and without Nb/ZnO NPs were compared. It was found that niobium doping led to a slight increase in open circuit voltage and an increase in short-circuit current. The effect of co-solvent (1,3,5-trichlorobenzene; TCB) in chlorobenzene in the polymer solution was also investigated on the morphology and performance of a P3HT:PCBM and P3HT:PCBM:Nb/ZnO bulk-heterojunction solar cells. The device efficiency was improved due to a good quality of the thin film nanostructure and annealing time. Copyright © Taylor & Francis Group, LLC.